Defragmenting Student Construction Holes in Solving System of Absolute Value Equations - Putri, Rizky Widya; Indrawatiningsih, Nonik (Universitas Negeri Surabaya, 2023)
Constructing concepts is one of the processes in learning mathematics. Making mistakes in constructing concepts is often experienced by students in solving mathematical problems, errors in constructing concepts that can be experienced are construction pits. Construction holes can occur if the schemes that are formed in the thinking structure of students have not been fully constructed or not, students cannot construct concepts properly and completely. This research is a descriptive study with a qualitative approach that aims to defragment the students' construction holes in solving systems of equations in the linear absolute value of one variable. The subject of this study was a class X high school student who fit the indicator for defragmenting the construction pit that is answering correctly but there was a construction process that was not appropriate and students answering correctly but the concept was not fully constructed. Data collection was carried out using test and interview instruments and analyzed ie reducing data, presenting data and drawing conclusions. The validity of the data is done by passing triangulation by comparing test results with interview results. From the results of this study it was found that students 'construction holes were located when simplifying absolute values ​​and determining the values ​​of and were therefore given defragmenting by providing conflict cognitive to sensitize students' mistakes in simplifying absolute values ​​and then new schemes emerged through scaffolding so that schemes were not constructed in a constructional manner. complete when determining the values ​​of and can be completely constructed.